Development of collaborative design environment with heterogenous CAD systems - Chen, Junyong (2008)
This research extends the field of collaborative CAD from one specific CAD system to multiple CAD systems and makes efforts to develop a collaborative design environment to support a set of heterogeneous CAD systems such that a product can be co-modeled simultaneously among a team of designers at geographically distributed locations. Four major issues are identified in developing a prototype system. They are: 1) feature-level interoperability; 2) network load and CAD data representation; 3) synchronization and consistency; and 4) concurrency. An operation-based solution is proposed to deal with these issues. Within the solution, a novel approach that uses operation as the basic transmission data unit to address feature-level interoperability is proposed. Based on the solution, the architecture of a collaborative system is proposed and detailed functional modules in this architecture are explained. An administrator/controller mechanism to improve efficiency and stableness is employed in the proposed system. The preliminary prototype system is developed based on two commercial CAD systems, Unigraphics and SolidWorks. A nearly real-time collaborative design has been realized. The experimental results from the prototype system have shown the feasibility of the novel method, which addresses feature-level interoperability and realizes dynamic high-level CAD data sharing/exchange among different CAD systems.